2021
DOI: 10.1186/s40168-020-00969-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between habitual diet, metabolic disease, and the gut microbiota using latent Dirichlet allocation

Abstract: Background The gut microbiome impacts human health through various mechanisms and is involved in the development of a range of non-communicable diseases. Diet is a well-known factor influencing microbe-host interaction in health and disease. However, very few findings are based on large-scale analysis using population-based studies. Our aim was to investigate the cross-sectional relationship between habitual dietary intake and gut microbiota structure in the Cooperative Health Research in the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 71 publications
7
45
0
Order By: Relevance
“…Both parameters continued to partition the community without reaching a clear optimum. This finding is unexpectedly consistent with recent publications using LDA in microbial ecology [4648]. Bacteria probability distributions (ranked by probability ≥ 1% in descending order) across the subgroups are displayed in Figure 6a.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Both parameters continued to partition the community without reaching a clear optimum. This finding is unexpectedly consistent with recent publications using LDA in microbial ecology [4648]. Bacteria probability distributions (ranked by probability ≥ 1% in descending order) across the subgroups are displayed in Figure 6a.…”
Section: Resultssupporting
confidence: 91%
“…We next tested LDA potential to stratify gut microbiota of the cohort participants. This unsupervised machine learning technique is increasingly finding acceptance in the field of microbiome [4648] for its unique ability to reveal latent or hidden groups within the data cloud. Supplementary Figure S4 shows LDA model’s perplexity parameter and log-likelihood values to find optimal number of clusters.…”
Section: Resultsmentioning
confidence: 99%
“…This bacterium has also been reported in diabetes. This conclusion is similar to the structure of this study [31]. The genus Actinomyces is widely distributed in nature and has a wide variety of species.…”
Section: Discussionsupporting
confidence: 92%
“…and [31]. In our heat map of differential bacteria and biochemical indicators, it is suggested that the genus Gemmiger is surely negatively correlated with the percentage of neutrophils, suggesting that genus Gemmiger is likely to play a role through immune regulation.…”
Section: Discussionmentioning
confidence: 79%
“…It should be noted that comorbidity was widespread among older adults with frailty and has been considered synonymous with frailty (Fried et al, 2001). However, many frailty-related diseases such as hypertension and diabetes have been reported to be associated with gut microbiota (Breuninger et al, 2021). We recorded the variables of drinking and smoking at present in the healthy control group and frail group.…”
Section: Discussionmentioning
confidence: 99%